Owl in love - Kindl, Patrice (Boston : Houghton Mifflin, 1993)
A fourteen-year-old girl, who can transform herself into an owl at will, discovers interesting new relationships with both humans and owls when she develops a crush on her science teacher.
Keywords: Supernatural; Teacher-student relationships -- Fiction